Learning to Measure Stereoscopic S3D Image Perceptual Quality on the Basis of Binocular Rivalry Response - Siyuan Huang; Wujie Zhou (Applied Sciences, 2019)
Blind perceptual quality measurement of stereoscopic 3D (S3D) images has become an important and challenging issue in the research field of S3D imaging. In this paper, a blind S3D image quality measurement (IQM) method that does not depend on examples of distorted S3D images and corresponding subjective scores is proposed. As the main contribution of this work, we replace human subjective scores with a quality codebook of binocular rivalry responses (BRRs); this allows blind S3D-IQM methods to be learned without evaluation performance loss. Our results, using the publicly accessible LIVE S3D dataset, confirm that our method is highly robust and efficient.